2009
DOI: 10.1515/cclm.2009.257
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study on the relationship between HDL2b and non-alcoholic fatty liver disease in Chinese type 2 diabetic patients

Abstract: Background: It has been shown that low concentrations of high-density lipoprotein cholesterol (HDL-C) are associated with non-alcoholic fatty liver disease (NAFLD) in patients with type 2 diabetes mellitus (T2DM). HDL2b, a major subfraction of high-density lipoprotein (HDL), is more significantly correlated with coronary heart disease (CHD) compared with total HDL. In this study, we analysed HDL2b in a cohort of Chinese T2DM subjects with or without NAFLD. Methods: A highly sensitive and reliable microfluidic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Compared with TC, TG should be a more appropriate independent risk factor for fatty liver. Studies have shown that serum TG was a significant risk factor for fatty liver [32], while TC was predominantly correlated with coronary atherosclerotic cardiopathy [33]. Given that A.muciniphila II had a more remarkable effect on TC, A.muciniphila II may act more strongly in regulating cholesterol metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with TC, TG should be a more appropriate independent risk factor for fatty liver. Studies have shown that serum TG was a significant risk factor for fatty liver [32], while TC was predominantly correlated with coronary atherosclerotic cardiopathy [33]. Given that A.muciniphila II had a more remarkable effect on TC, A.muciniphila II may act more strongly in regulating cholesterol metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a microfluidic chip-based technique is developed. This fast, easy-to-operate technique is successfully applied to measure the HDL subclasses in the epidemiological studies 15,16 .…”
mentioning
confidence: 99%